Formation of Liquid Products at the Filtration Combustion of Solid Fuels - E. A. Salgansky; V. M. Kislov; S. V. Glazov; M. V. Salganskaya (Journal of Combustion)
Yields of liquid and gaseous products of the filtration combustion of cellulose, wood, peat, coal, and rubber have been investigated. Experiments have shown that the gasification of solid fuels in the regime with superadiabatic heating yields liquid hydrocarbons with quantity and quality, which are close to those produced using other methods, for example, by pyrolysis. But in this case no additional energy supply is needed to carry out the gasification process. The low calorific combustible gas, which forms in this process, contains a substantial quantity of carbon monoxide and hydrogen, which are components of syngas.